MicroRNAs and angiosarcoma: are there promising reports? - Modarresi Chahardehi, Amir; Afrooghe, Arya; Emtiazi, Nikoo; Rafiei, Sajjad; Rezaei, Negin Jafarkhanloo; Dahmardeh, Sarvin; Farz, Fatemeh; Naderi, Zahra; Arefnezhad, Reza; Motedayyen, Hossein (Frontiers in Oncology, 2024)
In recent years, microRNAs (miRNAs) have garnered increasing attention for their potential implications in cancer pathogenesis, functioning either as oncogenes or tumor suppressors. Notably, angiosarcoma, along with various other cardiovascular tumors such as lipomas, rhabdomyomas, hemangiomas, and myxomas, has shown variations in the expression of specific miRNA subtypes. A substantial body of evidence underscores the pivotal involvement of miRNAs in the genesis of angiosarcoma and certain cardiovascular tumors. This review aims to delve into the current literature on miRNAs and their prospective applications in cardiovascular malignancies, with a specific focus on angiosarcoma. It comprehensively covers diagnostic methods, prognostic evaluations, and potential treatments while providing a recapitulation of angiosarcoma's risk factors and molecular pathogenesis, with an emphasis on the role of miRNAs. These insights can serve as the groundwork for designing randomized control trials, ultimately facilitating the translation of these findings into clinical applications. Moving forward, it is imperative for studies to thoroughly scrutinize the advantages and disadvantages of miRNAs compared to current diagnostic and prognostic approaches in angiosarcoma and other cardiovascular tumors. Closing these knowledge gaps will be crucial for harnessing the full potential of miRNAs in the realm of angiosarcoma and cardiovascular tumor research.